An intercomparison study of ice thickness models in the Netherlands - E. I. F. De Bruijn; F. C. Bosveld; E. V. Van Der Plas (Tellus: Series A, Dynamic Meteorology and Oceanography, 2014)
Lake models account for the thermodynamic interaction between fresh water lakes and the atmosphere. During frost periods they predict ice thickness. A stand-alone version of the Fresh water Lake model (FLake) has been compared with the operational ice-growth model at the Royal Netherlands Meteorological Institute. Both models have been driven with various input data like observations and data from the Hirlam Aladin Research on Mesoscale Operational NWP In Europe (HARMONIE) model. The lake ice models are validated with indirect ice thickness measurements at Cabauw during the winter of 1996/1997 and with data from a voluntary observer network in the province of Friesland (The Netherlands) during the winter of 2012. FLake is shown to have predictive power and is competitive with the operational ice-growth model.